Binding and arresting: surface and pattern in a contemporary traditional Pacific building - Tina Engels- Schwarzpaul (Interstices, 2017)
In classical Pacific buildings, figures or textures like lalava (lashings) performed iconic and technical functions simultaneously. What happens when the latter are assigned to different methods? The Fale Pasifika at the University of Auckland (opened in 2004) shows that the figures’ binding features outlast their technical necessity. The building attracts a diverse audience — perhaps because in the right constellations it binds together ancestral knowledge and present practices, despite many concessions to alien regulations and rules of production. However, its Pacific atmosphere also attracts non-Pacific people.